Some Aspects of Ring Theory - Herstein, I. N.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
S. Amitsur: Associative rings with identities.- I.N. Herstein: Topics in ring theory.- N. Jacobson: Representation theory of Jordan algebras.- I. Kaplansky: The theory of homological dimension.- D. Buchsbaum: Complexes in local ring theory.- P.H. Cohn: Two topics in ring theory.- A.W. Goldie: Non-commutative localisation.
S. Amitsur: Associative rings with identities -- I.N. Herstein: Topics in ring theory -- N. Jacobson: Representation theory of Jordan algebras -- I. Kaplansky: The theory of homological dimension -- D. Buchsbaum: Complexes in local ring theory -- P.H. Cohn: Two topics in ring theory -- A.W. Goldie: Non-commutative localisation.
Keywords: Mathematics; Algebra; Differential equations, partial; Mathematics; Associative Rings and Algebras; Several Complex Variables and Analytic Spaces